UTILIZING SOCIAL MEDIA FOR ENVIRONMENTAL AWARENESS CAMPAIGNS - Damanik, Dedy Chrisman H (PT. Jurnal Center Indonesia Publisher, 2025)
Social media has become an effective platform for disseminating information and raising environmental awareness. This article explores how social media is utilized as a communication tool in environmental campaigns, focusing on strategies, challenges, and its impact on public awareness. Research indicates that social media plays a significant role in reaching broader audiences, accelerating information dissemination, and encouraging public participation in environmental actions. However, challenges such as misinformation and unethical use of social media must also be addressed. This article provides recommendations to optimize social media in supporting sustainable environmental campaigns.